Analisis kesiapan profesi akuntan dalam era adaptasi kebiasaan baru - Inna Zahara; David Ulistiyantoro; Gerlan Haha Nusa (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2022)
This research aims to determine the standard of skills needed to be involved in the accounting profession in the era of new habits (new normal) adaptation. The standard is in line with data on job market demand for beginners in the accounting profession disclosed on the job market job sitedepnaker. The population and sample of the study were ten job openings, including the categories "audit and taxation," "banking or finance,";" Finance or Investment," and "General Accounting or Finance." The results of the first study showed that in the new normal era, the standard of skills needed to dabble in the accounting profession is based on data on job market demand disclosed on the job market job website, including having work experience and a certificate. Second, human resources are an essential part of another company's resources. One of the assessments of the quality of human resources can be seen from his work experience. Although beginner job openings are still needed, prospective employees with work experience of approximately one to two years are preferred. This can be understood because work experience becomes a plus for job seekers. With work experience, workers are more adaptable to fulfill their obligations.